Persistence of Examination Misconduct in Tertiary Institutions: Technology, Family, and Educational Institutions - Yarda, Muhammad Yahaya; Nazif, D. M. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study examines the persistence of examination misconduct in tertiary institutions, focusing on the roles of technology, family influence, and educational institutions in shaping students’ engagement in academic dishonesty. Using Gombe State Polytechnic, Bajoga (GSPB), and Federal Polytechnic Bauchi (FPTB) as case studies, the research employs a mixed-methods approach, including surveys and interviews, to assess the factors contributing to examination malpractice. The study explores how the widespread use of smartphones, smartwatches, and internet-enabled devices has transformed traditional cheating methods, making it easier for students to access unauthorized materials during exams. Findings indicate that technology has not only facilitated cheating but has also made detection more challenging due to the availability of encrypted communication channels and sophisticated cheating devices. In addition to technological factors, the study highlights the influence of family dynamics on students’ attitudes toward academic integrity. It was discovered that parental pressure to succeed, financial constraints, and limited parental involvement in students’ education contribute significantly to examination misconduct. Some parents, either knowingly or unknowingly, encourage academic dishonesty by emphasizing results over ethical learning, sometimes going so far as to hire proxy candidates or pay bribes to ensure their children pass. The research also reveals that students from families that prioritize integrity and moral upbringing are less likely to engage in cheating. Institutional policies and enforcement mechanisms also play a crucial role in either deterring or enabling examination malpractice. The study finds that weak implementation of academic integrity policies, lack of strict invigilation, overcrowded examination halls, and inadequate technological tools for monitoring contribute to the persistence of cheating. While some institutions have adopted anti-cheating technologies such as plagiarism detection software and biometric authentication, their effectiveness is often compromised by infrastructural deficiencies, poor enforcement, and lack of staff training. To address these challenges, the study recommends a multi-pronged approach, including the integration of advanced monitoring systems such as artificial intelligence-based surveillance, biometric verification, and stringent penalties for offenders. It also advocates for reinforcing ethical education in curricula, increased parental engagement in students' academic and moral development, and improved training for invigilators and academic staff on detecting and preventing cheating. Additionally, institutions should strengthen their examination policies, ensure consistent enforcement, and invest in research-driven strategies to curb academic dishonesty.